3D nanoweb-like zeolitic imidazole framework in a microfluidic system for catalytic applications. Issue 6 (15th May 2020) - Ko, Dong-Hyeon; Chen, Rui; Sun, Dengrong; Leem, Jin Woo; Joo, Jeong-Un; Kang, Il-Suk; Sung, Myung Mo; Lee, Haiwon; Kim, Dong-Pyo
Abstract : A 3D nanoweb-like zeolite imidazole framework (ZIF-8) as an efficient heterogeneous catalyst was structured inside a microfluidic channel for Knoevenagel condensation reaction by growing the ZIF on 3D carbon nanotube (CNT) networks bridging the built-in micropillars. Abstract : A 3D nanoweb-like zeolite imidazole framework (ZIF-8) as an efficient heterogeneous catalyst was structured inside a functionalized microfluidic channel by immobilizing the ZIF on 3D carbon nanotube (CNT) networks across the gap among the built-in micropillars for the Knoevenagel condensation reaction. The quantitative conversion was achieved under mild conditions of ethanol solvent and room temperature. The ZIF-8 3D nanoweb systems showed higher conversion than the identical systems without CNT-based networks which indicates the catalytic superiority of 3D nanoweb structures.